КИСЛОРОДЛИ ҚЎНДИРМАЛАРНИНГ АВТОБЕНЗИН КОМПОНЕНТЛАРИНИНГ ЧЎКМА ҲОСИЛ ҚИЛИШ ХОССАЛАРИГА ТАЪСИРИ - Махмудов, М.Ж.; муҳандислик, Бухоро; Суяров, М.Т. (SCIENCE and SOCIETY, 2022)
Studied osmolality mixtures pitches gasolines of different nature with different content of actual. It is proved that osmolality mixtures of gasoline is non-additive in nature. The introduction of oxygenates in the composition of gasoline of different nature leads to a decrease in their osmolality. Low-molecular alcohols and amines, as well as esters of the MTBE type, have a greater positive synergistic effect.
Keywords: motor gasoline; oxygenate synergistic; additive; reformate; catalyst; induction period